Survei Keterampilan Dribbling Peserta Ekstrakulikuler Futsal Di Sekolah Dasar Negeri 19 Kota Bengkulu - Ramadhan, Reza Trio; Ertanto, Dody; Apriansyah, Dolly (Educative Sportive, 2024)
Futsal extracurricular activities at Sekolah Dasar Negeri 19 Kota Bengkulu are a favorite and in high demand. Sports extracurricular activities at Sekolah Dasar 19 Kota Bengkulu are determined by the principal based on students' talents and interests. This investigate could be a quantitative think about that employments overview investigation methods. The populace of this ponder was 24 understudies from SD Negeri 19 in Bengkulu, and add up to inspecting procedure was utilized to gather the test. The comes about appeared that most of the understudies of SD Negeri 19 in Bengkulu city were capable in playing futsal.This study aims to determine how proficient SD Negeri 19 students in Bengkulu city are in futsal dribbling. This research is a quantitative research with survey analysis technique. The study population was 24 students from SD Negeri 19 in Bengkulu. The results of the study show that 24 futsal players have fairly good dribbling ability. Great spilling strategy, the correct choice, satisfactory physical capacity, and strategic understanding of the amusement are a few of the variables that influence the quality of spilling. The test was collected utilizing add up to examining strategy. Agreeing to the comes about of the ponder, most understudies of SD Negeri 19 in Bengkulu city have the capacity to play futsal.